THE FUNDAMENTAL TAKHREEJ OF MATAN AL-KUDDURI- PURITY AS A MODEL - SABAH, HASHEM; AL-ISSAWI, HASHEM; KHALID, BAN (Islamic Sciences Journal, 2023)
The origins of jurisprudence from the most honorable of science are a measure, the most prominent of which is a male, and the greatest in terms of rhetoric is injustice, as the hard-working people emerged in it as reasoning and luminance, and they lit up in ways that the judgments of accidents and calamities were enlightened by light, so we had to go into the midst of this science, especially as our teachers instructed us to write so that this knowledge of Great importance in devising legal rulings, and I hesitated a lot in writing on this topic, because I did not know little of this knowledge, but with the encouragement of my distinguished teachers, and after my reliance on Allah, I decided to write in it to learn and know how hard-working mujtahid and scholars were and how their deductions were For judgments, my research was it is entitled: The Fundamental Takhreej of Matan Al-Kadduri (Purity as a Model).